2012
DOI: 10.1159/000339760
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of IgE Binding to the Chitinase and Chitinase-Like House Dust Mite Allergens Der p 15 and Der p 18 Compared to the Major and Mid-Range Allergens

Abstract: Background: The prevalence of IgE binding to the group 15 and 18 house dust mite (HDM) allergens of the Dermatophagoides species is reported to be >50% and they are the major allergens of HDM-sensitised dogs. The objective was to quantitate the IgE titres to Der p 15 and Der p 18 and evaluate their importance in human HDM sensitisation compared to the known major and mid-tier allergens. Methods: Der p 15 and Der p 18 were produced in Pichia pastoris, and their structure validated by circular dichroism. IgE bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…A recent report demonstrated that asthmatic children had an expanded IgE repertoire with more recognized allergen components (Der p 1, Der p 2, Der p 5 and Der p 23) and increased sIgE levels than nonasthmatic children [30] . Other minor components contributed less to IgE binding quantity than Der p 1 and Der p 2 [31] . Kidon et al [17] have shown that sIgE responses to an increased number of distinct mite allergens correlates with the complexity of the allergic phenotype, and that both Der p 1 and Der p 2 are risk factors for multisystemic phenotypes of allergic diseases in Singapore.…”
Section: Discussionmentioning
confidence: 86%
“…A recent report demonstrated that asthmatic children had an expanded IgE repertoire with more recognized allergen components (Der p 1, Der p 2, Der p 5 and Der p 23) and increased sIgE levels than nonasthmatic children [30] . Other minor components contributed less to IgE binding quantity than Der p 1 and Der p 2 [31] . Kidon et al [17] have shown that sIgE responses to an increased number of distinct mite allergens correlates with the complexity of the allergic phenotype, and that both Der p 1 and Der p 2 are risk factors for multisystemic phenotypes of allergic diseases in Singapore.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, other replacements that seem to be relevant in the differential binding activity are two proline residues, only present in the second isoform, which are known to influence loop formation. Other HDM allergens such as the peritrophin Der p 23 [37] and the chitinase Der p 15 [42,43] also contain a CBD, but their sequence similarity with Blo t 12 was rather low. This is in agreement with the lack of reactive components to anti-Blo t 12-specific polyclonal and monoclonal antibodies in D. pteronyssinus extracts (Zakzuk et al, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Two versions of the chip have been made, one which contains a collection of enterotoxins from Staphylococcus aureus involved in respiratory allergies [44] and another comprising an extended panel of antigens relevant for hypersensitivity to wheat [29,30,[45][46][47]. Considering the poor quality of natural house dust mite allergen extracts, we aimed to implement a panel of purified house dust mite allergens that is as complete as possible [48][49][50]. Furthermore, several cockroach allergens were included [51,52].…”
Section: Examples Of Detecting Early Allergen-specific Ige Responses mentioning
confidence: 99%